Intestinal and fecal pH in human health - Yamamura, Ryodai; Inoue, Kumi Y.; Nishino, Kunihiko; Yamasaki, Seiji (Frontiers in Microbiomes, 2023)
Gut microbiota has been reported to be closely related to host energy metabolism and immunity, and thus influence the development and progression of various human diseases. To date, the gut microbial metabolites such as short-chain fatty acids, defensins, cathelicidins, and lactoferrin in feces have been investigated as biomarkers associated with various disease conditions. In this review, we introduce fecal pH, which is relatively easy and rapid to measure compared to the composition of the gut microbiota and its metabolites. In particular, this review presents the distribution of pH in the human body, its role and clinical significance, and various factors that affect fecal pH, including the gut microbiota and its metabolites.